2022
DOI: 10.1016/j.amjoto.2021.103220
|View full text |Cite
|
Sign up to set email alerts
|

COVID associated mucormycosis: A preliminary study from a dedicated COVID Hospital in Delhi

Abstract: Background It is an incontrovertible fact that the Rhino Orbital Cerebral Mucormycosis (ROCM) upsurge is being seen in the context of COVID-19 in India. Briefly presented is evidence that in patients with uncontrolled diabetes, a dysfunctional immune system due to SARS-COV-2 and injudicious use of corticosteroids may be largely responsible for this malady. Objective To find the possible impact of COVID 19 infection and various co-morbidities on occurrence of ROCM and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
5
24
1
Order By: Relevance
“…[ 47 ] India Retrospective Single-center 11 Feb 2020–May 2021 47 ± 11 100 (11) 64 (7) Fouad YA. [ 48 ] Egypt Retrospective Single-center 26 Apr 2021–Aug 2021 63 [46–70] 54 (14) 96 (25) Meher R. [ 49 ] Iran Prospective Single-center 111 May 2021–Jun 2021 53 ± 12 70 (78) 94 (104) Guzman-Castro S. [ 50 ] UK Retrospective Single-center 6 May 2021 52 [45–57] 83 (5) 83 (5) Kumar H. [ 51 ] India Retrospective Single-center 28 Apr 2021–May 2021 54 [48–59] 79 (22) 75 (21) Yadav T. [ 52 ] India Retrospective Single-center 50 Dec 2020–Jun 2021 50 [28–70] 62 (31) 86 (43) Meshram HS. [ 53 ] India Retrospective …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47 ] India Retrospective Single-center 11 Feb 2020–May 2021 47 ± 11 100 (11) 64 (7) Fouad YA. [ 48 ] Egypt Retrospective Single-center 26 Apr 2021–Aug 2021 63 [46–70] 54 (14) 96 (25) Meher R. [ 49 ] Iran Prospective Single-center 111 May 2021–Jun 2021 53 ± 12 70 (78) 94 (104) Guzman-Castro S. [ 50 ] UK Retrospective Single-center 6 May 2021 52 [45–57] 83 (5) 83 (5) Kumar H. [ 51 ] India Retrospective Single-center 28 Apr 2021–May 2021 54 [48–59] 79 (22) 75 (21) Yadav T. [ 52 ] India Retrospective Single-center 50 Dec 2020–Jun 2021 50 [28–70] 62 (31) 86 (43) Meshram HS. [ 53 ] India Retrospective …”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] 45 (5) 100 (11) 100 (11) 36 (4) 0 (0) 36 (4) Fouad YA. [ 48 ] 27 (7) 12 (3) 77 (20) Meher R. [ 49 ] 27 (30) 5.4 (6) 60 (67) 5.4 (6) Guzman-Castro S. [ 50 ] 50 (3) 33 (2) 100 (6) Kumar H. [ 51 ] 57 (16) 21 (6) 68 (19) Yadav T. [ 52 ] 2.0 (1) 38 (19) 44 (22) Meshram HS. [ 53 ] 100 (61) 100 (61) 67 (41) 0 (0) …”
Section: Resultsmentioning
confidence: 99%
“… 18 Another indirect potential correlation has been established between COVID-19 and mucormycosis in India is the use of contaminated water with fungal spores for oxygen humidifier or use of contaminated and poor quality industrial oxygen during the shortfall of medical oxygen during the second wave of COVID-19 infection. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that their data should be compared to data from Western countries, where the main predisposing factor for mucormycosis are hematological malignancies and organ transplantation, apart from diabetes mellitus. Several other cohorts reported the frequency of GCS use among CAM patients as high as 60% [ 104 , 105 ], over 85% [ 106 , 107 ] and 100% [ 107 ]. With regards to Pneumocystis jirovecii Pneumonia (PJP), Chong et al [ 108 ], in their excellent review of PJP-SARS-CoV-2 co-infection case reports, conclude that the virus may predispose to this fungal entity through lymphocytopenia and macrophage dysfunction.…”
Section: Immunosuppressive Therapy As Risk Factor For Fungal Infectio...mentioning
confidence: 99%